Security–Energy Nexus in Indonesia’s Border: The Case of Natuna - Purnomo Yusgiantoro; Utjok WR Siagian; Agus HS Reksoprodjo; Debby RA Gustin; Novena Damar Asri (Purnomo Yusgiantoro Center, 2024)
Natuna is one of the outmost islands in northern Indonesia. Natuna is vital as it delimits Indonesia’s territorial and deposits abundant energy resources. However, Natuna is also vulnerable, as it is adjacent to (and is partly located in) the South China Sea, a flash point in the region. As the sea is rich in natural resources, many countries around the sea are competing to control it, which leads to disputes. This study combines a literature review with interviews and finds that the risk of threats in the Natuna area encourages Indonesia to establish a military base there. The military base plays a role in securing Indonesia’s sovereignty over the Natuna area, including energy resources, an essential resource for the economy and development. This study proposes a new notion of ‘energy resource effects’ that influence the development of the situation and Indonesia’s decision to build a military base in the Natuna area. The energy-security nexus, thus, implies the close relationships between energy and security and how the two affect each other. Finally, this study also offers Indonesia’s perspective on securing its border areas, especially those rich in energy resources.